AFFIRM ROLE OF EXISTENCE RECHTSVERWERKING TO ACHIEVING LEGAL CERTAINTY IN LAND REGISTRATION - Rofiq laksamana; Setiono Setiono; I Gusti Ayu Ketut Rachmi Handayani; Oloan Sitorus (The 2nd Proceeding “Indonesia Clean of Corruption in 2020", 2020)
The purpose of this research was to exemine the principle of rechtsverwerking  were formulated in the national land law, primarily  on the Government Regulation concerning land registration and it aplication on the Court’s desicition.Rechtsvewerking is a principle in adat law which states that owner ofa parcel of land that leaves his land abandoned in certain period of time and lets otherpeople to occupy andtake advantage will cause the original owner to lose his right ofthe land, is established to overcome the weakness of the land registration system.  This study uses normative legal research methods, with  statute approach, and consepual approach. Legal materials were analyzed by syllogism of induction, deduction and interpretation.  The results showthe principle of rechtsverwerkingis embodied in the regulation of land registraion called GR No. 24 of 1997. The Regulation provide that the issuance of a certificate for an applicant who has mastered the ground in a certain period of time has been acquired in good faith and registered in his name, then others who feel have an interest, then by law only given the opportunity during the time period of five years.However in law enforcement inside the court this principle tends to be deserted therefore creates an certainty in law and unfairness to people who have occupied a land in a longperiod oftime.